2002
DOI: 10.1242/jeb.205.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body hyperthermia-induced thermotolerance is associated with the induction of Heat Shock Protein 70 in mice

Abstract: SUMMARY Molecular mechanisms of whole-body thermotolerance (WBT) in mammals have not been investigated thoroughly. The purpose of this study was to assess the induction of the 70 kDa heat shock protein (HSP70) and antioxidant enzyme activity in animal WBT, which was induced by whole-body hyperthermia (WBH) in mice. As a preconditioning treatment, WBH was applied to mice to induce WBT. Synthesis of inducible HSP70 (HSP70i) and quantification of its increased level in liver were investigated by on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(4 citation statements)
references
References 37 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…We have previously showed that synthesis of HSP70 in liver induced by whole body hyperthermia is associated with the survival in mice and the survival rate (88.2%) of animals subjected to preconditioning markedly exceeded that of the control group (37.5%) (King et al, 2002). Because of failure to express detectable level of HSP70, we could not demonstrate the protein function in HSP70 transgenic mice driven by CMV promoter (the same construct used in this study).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We have previously showed that synthesis of HSP70 in liver induced by whole body hyperthermia is associated with the survival in mice and the survival rate (88.2%) of animals subjected to preconditioning markedly exceeded that of the control group (37.5%) (King et al, 2002). Because of failure to express detectable level of HSP70, we could not demonstrate the protein function in HSP70 transgenic mice driven by CMV promoter (the same construct used in this study).…”
Section: Discussionmentioning
confidence: 64%
“…A plenty of studies have documented thermotolerance in cultured cells and in animals other than mammals (Laszlo and Li, 1985;Mizzen and Welch, 1988;Ulmasov et al, 1992;Kampinga, 1993;Mosely, 1997;Theodorakis et al, 1999). Presently, few studies revealed that thermotolerance in mice can be induced by whole body hyperthermia (Kapp and Lord, 1983;Weshler et al, 1984;King et al, 2002). Moreover, the correlation between myocardial injury due to ischemia and the expression of inducible HSP70 under the control of β-actin promoter in transgenic mice has been reported (Marber et al, 1995;Hutter et al, 1996;Trost et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…HSPs may play important roles in protein assembly and disassembly (Bukau et al, 2000;Hartl and Hayer-Hartl, 2002), protein folding and unfolding (Hartl, 1996;Mayer and Bukau, 2004;Zietkiewicz et al, 2004), protein translocation (Ryan and Pfanner, 2001), and the refolding of damaged proteins (Hightower, 1991;Glover and Lindquist, 1998;Maloyan et al, 1999). Of the many expressed HSPs, those with a molecular weight of approximately 70 kDa appear to be most closely associated with heat tolerance (Craig and Gross, 1991;Wang and Edens, 1998;King et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…HSPs are released intra cellularly and extra cellularly in response to various environmental stresses (Sonna et al 2002, Hecker et al 2011) in inducible form and can be an indicator of stress in cells (Sonna et al 2002). The regulation of HSP production is critical to cell survival and among the HSPs, Hsp70 has a significant role in cell thermo-tolerance and animal survival (King et al 2002). Understanding the regulation of heat stress at cellular level and expression pattern of Hsp70 gene will throw light on the mechanism of heat stress adaptation in goats.…”
mentioning
confidence: 99%